Rotator Interval Lesion and Damaged Subscapularis Tendon Repair in a High School Baseball Player - Tomoyuki Muto; Hiroki Ninomiya; Hiroaki Inui; Masahiko Komai; Katsuya Nobuhara (Case Reports in Orthopedics)
In 2013, a 16-year-old baseball pitcher visited Nobuhara Hospital complaining of shoulder pain and limited range of motion in his throwing shoulder. High signal intensity in the rotator interval (RI) area (ball sign), injured subscapularis tendon, and damage to both the superior and middle glenohumeral ligaments were identified using magnetic resonance imaging (MRI). Repair of the RI lesion and partially damaged subscapularis tendon was performed in this pitcher. During surgery, an opened RI and dropping of the subscapularis tendon were observed. The RI was closed in a 90° externally rotated and abducted position. To reconfirm the exact repaired state of the patient, arthroscopic examination was performed from behind. However, suture points were not visible in the >30° externally rotated position, which indicates that the RI could not be correctly repaired with the arthroscopic procedure. One year after surgery, the patient obtained full function of the shoulder and returned to play at a national convention. Surgical repair of the RI lesion should be performed in exactly the correct position of the upper extremity.